Performance analysis of voltage sensorless based controller for two-stage grid-connected solar PV system - Meghraj Morey; Nitin Gupta; Man Mohan Garg; Ajay Kumar (Institute of Advanced Engineering and Science, 2023)
In this research, a sensor free DC-link voltage controller based multifunctional inverter is proposed for a two-stage three-phase grid-connected solar photovoltaic (PV) system. First, the proposed scheme consists of an outer voltage controller requiring DC-link voltage knowledge, has the ability to manage power-sharing between the PV system and the utility grid, and second, has the ability of the VSI to act as a compensator for harmonics in the grid current polluted by non-linear loads. The suggested active power controlling grid reference current signal scheme replaces the standard controller, requiring the high voltage sensor to sense DC-link voltage, which is pricey, increasing the hardware complexity and reducing reliability. The performance of the proposed active power management approach is comparable to that of a conventional voltage sensor-based voltage controller. The effectiveness of the proposed method for two stage three-phase grid-connected solar PV system under fixed and variable irradiance feeding nonlinear loads is rigorously verified using MATLAB/Simulink software.